The Need for Stump-Socket Interface Pressure Measurment during Bidirectionally Perturbed Stance In Transtibial Amputees - Shirazi, S.Y.; Safaeepour, Z.; Seddighi, Amir Saied; Fatouraee, N. (International Clinical Neuroscience Journal, 2015)
Recent studies show significant reduction of postural stability in transtibial amputees (TTAs) especially when a perturbation is applied. However, no record has been seen on the consequences of such perturbation on the Stump-Socket Interface Pressure (SSIP). Our objective was to investigate whether such perturbation impose excessive pressures on the stump. We were also interested on the type of the response and direction in which TAs may face more difficulties. A 52-year-old TA participated in the study. The trial was performed using a custom bidirectional perturbing mechanism in the pitch and roll axes of ankle. Center of Pressure and were recorded by two force platforms and five resistive pressure sensors respectively. Right and anterior perturbations imposed the maximum SSIP while several CoP measures were considerably greater for the prosthetic leg just in left perturbations. This supports the necessity of measurement of SSIP as well as CoP to provide a better understanding about the new situations of TAs in postural stability